The After-Office-Hour Nursing Supervision Model Development at Buddhachinaraj Phitsanulok Hospital - Suwannapap, Duangta; Tammakun, Thana; Seubsaion, Sanong; Homsuwan, Rungphetch (Journal of Health Science of Thailand, 2019)
The purpose of this study was to develop and evaluate the effectiveness of a stakeholders were after-office-hour nursing supervisory model. BuddhachinarajPhitsanulokHospital. The developmental process consisted of 3 stages 1) problems and needs identification 2) constructed a model 3) evaluation of model effectiveness. The study was carried out during April 2006-May 2007. 105 nursing supervisors. The research instrument was a questionnaire on the supervisors satisfaction. Data analysis by using frequency, percentage, mean and standard deviation. A part-time nursing supervisory model consist of 1) appropriate numbers of part-time nurse supervisors were provided: providing knowledge for nurse supervisors, establishing nurse administrative committee as a consultative committee 2) identify part-time supervisor job deseription and authority 3) superviaorีs record developed 4) place, materials and other facilities supporting supervision were provided At the end of study, the supervisor had more satisfaction with the constructed model.